Pattern of Bacteria and Its Susceptibility of Ventilator-Associated Pneumonia Patients in ICU at Dr. Hasan Sadikin General Hospital, Bandung - Jundi, Achmad Faisal; KSS, Nurita Dian; Mulyana, Yanti (Althea Medical Journal, 2016)
Background: Incidence of ventilator-associated pneumonia (VAP) is common in intensive care unit (ICU).Â This pneumonia, becomes important due to its association to increased length of hospital stay, increasedÂ costs, and increased mortality. Irrational administration of antibiotics can lead to development of bacterialÂ resistance. The objective of this study was to describe the pattern of bacteria and the susceptibility of VAPÂ patients.Methods: A descriptive study was carried out to 10 medical records of VAP patients in the ICU at Dr. HasanÂ Sadikin General Hospital, Bandung in JanuaryâJune 2014. Microbiological culture results and antibioticsÂ susceptibility testing of patientsâ sputum were identified and the collected data were analyzed in form ofÂ tables and percentages by using a computer program.Results: Out of 44 cultures taken from 10 patients with VAP, 43 cultures had microbiological findings.Â Gram negative bacteria were found in 90.6% cultures, the rests were Gram positive bacteria and fungi.Â The majority of findings were: Acinetobacter baumannii (41.9%), Pseudomonas aeruginosa (18.6%), andKlebsiella pneumoniae (16.9%). The laboratory test result showed varied degrees of antimicrobial resistanceÂ to antibiotics.Conclusions: Bacteria found in sputum cultures of ICU patient with VAP are mostly of Gram negative. TheÂ result of susceptibility testing of bacteria shows many of the bacteria have resistance to antibiotics in ICU atÂ Dr. Hasan Sadikin General Hospital. [AMJ.2016;3(2):195â9]DOI:Â 10.15850/amj.v3n2.772